Severe thrombocytopenia induced by niraparib in ovarian cancer patients: a case report and literature review - Li, Jiajun; Yang, Jiaxi; Wang, Ying (Frontiers in Oncology, 2025)
Ovarian cancer (OC) is a common gynecological malignancy, and poly (ADP-ribose) polymerase inhibitor (PARPi) maintenance therapy has significantly prolonged the survival of newly diagnosed or platinum-sensitive recurrent ovarian cancer patients, which has become a new treatment paradigm for ovarian cancer. Niraparib is a widely used PARP inhibitor in the clinical setting, and its adverse effects are also a major concern. The common adverse reactions of Niraparib mainly include various hematological adverse reactions (such as thrombocytopenia and anemia), gastrointestinal adverse reactions (such as nausea and vomiting), and fatigue. In previous related reports, thrombocytopenia has been mentioned multiple times, a relatively common adverse reaction of Niraparib. However, there have been no reports of irreversible and persistent thrombocytopenia. This case report describes a 59-year-old woman who developed persistent thrombocytopenia 11 months after adjuvant chemotherapy for stage IIIC high-grade serous ovarian cancer. Despite various treatment measures, the patient’s platelet count continues to fluctuate and remains low. This is a severe thrombocytopenia that may rare adverse reaction caused by Niraparib. This article adds important information to the scientific literature on potential serious adverse reactions in long-term treatment with Niraparib. It emphasizes the necessity of closely monitoring platelet counts during Niraparib treatment.